Correction: Behavioral and psychosocial factors of quality of life among adult people living with HIV on Highly Active Antiretroviral Therapy, in public hospitals of Southwest Ethiopia. - Abreha Addis Gesese; Yitages Getachew Desta; Endale Zenebe Behire (Public Library of Science (PLoS), 2024)
[This corrects the article DOI: 10.1371/journal.pgph.0000822.].